1990
DOI: 10.1104/pp.94.4.1709
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Brassinosteroids from the Cambial Region of Scots Pine (Pinus silverstris) by Gas Chromatography-Mass Spectrometry, after Detection Using a Dwarf Rice Lamina Inclination Bioassay

Abstract: A simple and improved dwarf rice (Oryza sativa var Tan-ginbozu) lamina inclination bioassay for brassinosteroids (BRs) was developed based on a previously published method (K Takeno, RP Pharis [1982] Plant Cell Physiol 23: 1275-1281). The assay used 3-day-old intact seedlings, and detection of BR was made more sensitive by synergizing the response to BR with indole-3-acetic acid (IAA). The minimum detectable amount of BR was less than 0.1 nanogram/rice plant (brassinolide equivalents). Purification steps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…And typhasterol was about one-tenth as active as castasterone. These relative values for inclination activity are almost the same as those reported by a rice lamina inclination assay using a cultivar Koshihikari used as the most common rice cuitivar for detecting brassinosteroids (Kim et al, 1990). Thus our rice lamina inclination assay using a cultivar Tongjin is also useful for examination of brassinosteroids structure-activity relationship.…”
Section: Selection Of a Korean Rice Cultivar For A Rice Lamina Inclinsupporting
confidence: 76%
“…And typhasterol was about one-tenth as active as castasterone. These relative values for inclination activity are almost the same as those reported by a rice lamina inclination assay using a cultivar Koshihikari used as the most common rice cuitivar for detecting brassinosteroids (Kim et al, 1990). Thus our rice lamina inclination assay using a cultivar Tongjin is also useful for examination of brassinosteroids structure-activity relationship.…”
Section: Selection Of a Korean Rice Cultivar For A Rice Lamina Inclinsupporting
confidence: 76%
“…Furthermore, previous studies on the effects of BRs on vascular development indicated that BRs play a role in tracheary element formation (Clouse and Zurek, 1991;Iwasaki and Shibaoka, 1991). Because BRs also have been found in the cambial region of pine, indicative of an important role in this tissue (Kim et al, 1990), we hypothesize that the deficiency of BRs in dwarf mutants caused changes in cell fate in vascular cambial cells through yet unknown mechanisms. Accumulation of episterol with a simultaneous decrease of downstream intermediates, including 24-MC and CR, predicts that the C-5 desaturation step is blocked in dwf7-1 plants.…”
mentioning
confidence: 93%
“…Although, the existence of BRs in vascular cells of pine tree has been reported (Kim et al, 1990), it is still unknown if BRs are biosynthesized in the vascular tissues themselves. Mathur and others indicated that a chimeric CPD promoter-uid gene is strongly expressed in palisade cells, suggesting that a key enzyme for synthesizing BRs is expressed in mesophyll cells (Mathur et al, 1998).…”
Section: Brs Rapidly Increase Before Entry Into the Final Stagementioning
confidence: 99%